Motion in Games Second International Workshop, MIG 2009, Zeist, The Netherlands, November 21-24, 2009 - Egges, Arjan; Geraerts, Roland; Overmars, Mark (Image Processing, Computer Vision, Pattern Recognition, and Graphics, 2009)
This book constitutes the proceedings of the Second International Workshop on Motion in Games, held in Zeist, The Netherlands, in November 2009. The 23 papers presented in this volume were carefully reviewed and selected. The topics covered are avoidance behaviour, behaviour and affect, crowd simulation, motion analysis and synthesis, navigation and steering, physics, rendering and video. .